The role of special foreign language in the formation of professional competence of future specialists - Svetlana V. Krutskaya; Liliya R. Nurtdinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper deals with aspects and methods of special foreign language teaching. The definition of a term "special language" is formulated. Based on this definition, the characteristics of the phenomenon are considered. According to the reviewed features efficient methods for the selection of text material are given. The proposed division of texts can make teacher’s work more effective as it helps to organize materials according to increasing of their specialization. A number of criteria, which can be used by students when working with texts of special language, is suggested.